2017
DOI: 10.1098/rsos.160991
|View full text |Cite
|
Sign up to set email alerts
|

Social Reward Questionnaire—Adolescent Version and its association with callous–unemotional traits

Abstract: During adolescence, social interactions are a potent source of reward. However, no measure of social reward value exists for this age group. In this study, we adapted the adult Social Reward Questionnaire, which we had previously developed and validated, for use with adolescents. Participants aged 11–16 (n = 568; 50% male) completed the Social Reward Questionnaire—Adolescent Version (SRQ-A), alongside measures of personality traits—five-factor model (FFM) and callous–unemotional (CU) traits—for construct valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 55 publications
1
29
0
Order By: Relevance
“…We measured sensitivity to social rewards with the Dutch adolescent version of the Social Reward Questionnaire (Foulkes et al., ). We used only the sociability and prosocial interactions subscales because of their likelihood to be associated with giving to friends, classmates, and strangers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We measured sensitivity to social rewards with the Dutch adolescent version of the Social Reward Questionnaire (Foulkes et al., ). We used only the sociability and prosocial interactions subscales because of their likelihood to be associated with giving to friends, classmates, and strangers.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study showed that adolescents who displayed higher sensitivity to social rewards donated more to charity (Kwak & Huettel, ). In this study, we investigated associations between giving and two domains of social rewards, namely prosocial interactions (i.e., feeling rewarded by having kind, reciprocal relationships) and sociability (i.e., feeling rewarded by engaging in group interactions; Foulkes et al., ). These domains are expected to be associated with differences in giving to different peers (i.e., friends, classmates, and strangers) in adolescence.…”
Section: Adolescents’ Giving To Peers In Dictator Gamesmentioning
confidence: 99%
See 2 more Smart Citations
“…Both monetary and social rewards are widely used in scientific research (Izuma et al, 2008;Knutson et al, 2008;Kohls et al, 2009;Trezza et al, 2011;Forbes and Dahl, 2012;Guyer et al, 2012;Somerville, 2013;Stavropoulos and Carver, 2013;Leotti and Delgado, 2014;Weinberg et al, 2014;Foti et al, 2015;Olino et al, 2015;Anderson, 2016;Foulkes et al, 2017;Cao et al, 2018;Oldham et al, 2018;Altikulaç et al, 2019). Researchers have directly compared behavioral performances and neural responses to social and monetary rewards to investigate whether there were differences between them.…”
Section: Introductionmentioning
confidence: 99%